2013
DOI: 10.1088/1674-1056/22/3/037504
|View full text |Cite
|
Sign up to set email alerts
|

Defect types and room-temperature ferromagnetism in undoped rutile TiO2single crystals

Abstract: Room-temperature ferromagnetism has been experimentally observed in annealed rutile TiO2 single crystals when a magnetic field is applied parallel to the sample plane. By combining X-ray absorption near the edge structure spectrum and positron annihilation lifetime spectroscopy, Ti3+—VO defect complexes (or clusters) have been identified in annealed crystals at a high vacuum. We elucidate that the unpaired 3d electrons in Ti3+ ions provide the observed room-temperature ferromagnetism. In addition, excess oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Since the discovery of room temperature ferromagnetism in Co-doped TiO 2 thin films [ 63 ] understanding the causes of ferromagnetism in TiO 2 materials is a subject of lively discussion [ 64 , 65 , 66 , 67 , 68 , 69 ]. The hysteresis loop diagram for S1 resembles the results obtained in paper [ 70 ] for TiO 2 single crystals annealed in a high vacuum where the investigated samples were diamagnetic at room temperature with a characteristic low-field ferromagnetic behavior. In paper [ 70 ], it was concluded that the unpaired 3d electrons in Ti 3+ ions can be responsible for the observed room temperature ferromagnetism.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Since the discovery of room temperature ferromagnetism in Co-doped TiO 2 thin films [ 63 ] understanding the causes of ferromagnetism in TiO 2 materials is a subject of lively discussion [ 64 , 65 , 66 , 67 , 68 , 69 ]. The hysteresis loop diagram for S1 resembles the results obtained in paper [ 70 ] for TiO 2 single crystals annealed in a high vacuum where the investigated samples were diamagnetic at room temperature with a characteristic low-field ferromagnetic behavior. In paper [ 70 ], it was concluded that the unpaired 3d electrons in Ti 3+ ions can be responsible for the observed room temperature ferromagnetism.…”
Section: Resultssupporting
confidence: 81%
“…The hysteresis loop diagram for S1 resembles the results obtained in paper [ 70 ] for TiO 2 single crystals annealed in a high vacuum where the investigated samples were diamagnetic at room temperature with a characteristic low-field ferromagnetic behavior. In paper [ 70 ], it was concluded that the unpaired 3d electrons in Ti 3+ ions can be responsible for the observed room temperature ferromagnetism. In sample S1, a similar mechanism can explain its ferromagnetic properties at a weak magnetic field.…”
Section: Resultssupporting
confidence: 81%
“…This work presents a way to produce a magnetic layer at the surface of TiO 2 anatase by low-energy Ar + -ion irradiation [65]. Defect-induced magnetism in TiO 2 has been studied in the past [7,[66][67][68][69][70], achieving Curie temperatures of up to 880 K [10,69]. The main difference between our approach and those published is related to the low ion energy and fluences we use, which allow us to produce a robust magnetic layer close to the surface of the films.…”
Section: Introductionmentioning
confidence: 99%
“…Here a hypothesis is made that such heat do not or has little influence on the separation and migration of charge carriers. [64] and it could be seen that the potential field of the neighbouring Ti is The atomic lattice is blurred Maybe exists [72,123] Ultraviolet-visible spectroscopy (UV-vis) An optical absorption band above 400 nm Maybe exists [30] Photoemission spectroscopy (PL) The emission position and intensity Type, relative concentration of defects [124] Raman spectroscopy Variation in vibration of O and Ti-related region Type of defects [30,38,72] X-ray photoelectron spectroscopy (XPS) Valence state variation Type of defects mainly Ti 3+ [30,37,72,89] Electron paramagnetic resonance (EPR) factor calculated from the position of the sharp signal Type of paramagnetic defects [35,123,125,126] Positron annihilation lifetime spectroscopy (PALS) The lifetime of the positrons Size, type, and relative concentration of defects [68] Scanning tunneling microscopy (STM) Light dot in pictures The type, position of defects [31,113,120] Atomic force microscopy (AFM) Comparison of pictures The type, position of defects [38] Temperature programmed deoxidation (TPD) A narrow peak related to partial oxygen loss according to temperature. the most influenced site whereas the variations die largely in distance.…”
Section: Transient Local Heatmentioning
confidence: 99%
“…Considering the oxygen activity and temperature, surface treatment methods (e.g., annealing in vacuum condition [68], thermal treatment under reducing atmosphere (H 2 , CO, NO), and bombardment using electron beam [69,70], neutron, or -ray) are introduced to obtain defective surfaces. The bulk ODTs can be directly obtained from sputtering method without further modifications on the TiO 2 samples.…”
Section: Generation Of Otds In Tiomentioning
confidence: 99%